2012
DOI: 10.1021/ja3008566
|View full text |Cite
|
Sign up to set email alerts
|

Nature and Structure of Aluminum Surface Sites Grafted on Silica from a Combination of High-Field Aluminum-27 Solid-State NMR Spectroscopy and First-Principles Calculations

Abstract: The determination of the nature and structure of surface sites after chemical modification of large surface area oxides such as silica is a key point for many applications and challenging from a spectroscopic point of view. This has been, for instance, a long-standing problem for silica reacted with alkylaluminum compounds, a system typically studied as a model for a supported methylaluminoxane and aluminum cocatalyst. While (27)Al solid-state NMR spectroscopy would be a method of choice, it has been difficult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
109
2
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(118 citation statements)
references
References 81 publications
6
109
2
1
Order By: Relevance
“…2A, and consists of a prominent resonance centered at ∼33 ppm. The chemical shift of this resonance corresponds to previously reported five-coordinate aluminum centers in oxide materials (40,41). Similar resonances are measured with spin-echo pulse sequence for methyl Al(III)-calixarene complexes before anchoring, as shown in Fig.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…2A, and consists of a prominent resonance centered at ∼33 ppm. The chemical shift of this resonance corresponds to previously reported five-coordinate aluminum centers in oxide materials (40,41). Similar resonances are measured with spin-echo pulse sequence for methyl Al(III)-calixarene complexes before anchoring, as shown in Fig.…”
Section: Resultssupporting
confidence: 85%
“…The center resonances of all spectra in Fig. 2 are notably shifted away from 0 ppm, the expected chemical shift for octahedral aluminum species, and are within the range known for Al(III)-alkoxides and Al (III)-phenoxides (40,41). There are no AlMe 3 species remaining after reaction as verified via complete loss of calix [4]arene OH resonance in the 1 H NMR spectra as well as lack of the characteristic 155-ppm resonance in the 27 Al NMR spectrum.…”
Section: Resultssupporting
confidence: 70%
“…The type of reaction between alkyl aluminum compounds (AlR 3 , R = Me, 2934 Et, 35 iBu…) and silica surface still remains not elucidated despite its huge applications as a co-catalyst for olefins polymerization. 3639 Because many aluminum alkyls exist in solution as dimers or trimers, we have chosen triisobutylaluminum (TIBA) because it is a monomer, 40 with the hope it will remain monomeric once it is grafted to the surface.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the available data, the authors concluded that, under their experimental conditions, there is remarkable incorporation of Al into the framework of SBA15. 35,42 …”
Section: Introductionmentioning
confidence: 99%
“…The most shielded component (δ 33 ) is aligned along the p-orbital of the alkylidene ligand, as in sp 2 hybridized carbon, for weak agostic interactions; and approaches a M C alkylidyne type bond, as [18] sites formed upon Et 3 Al grafting on dehydroxlated SBA-15. [23] We reconstituted the structure of each surface site by aligning the experimental results with DFT calculations on cluster and periodic models. Two aluminum sites that correspond to a dinuclear Al species grafted either via two terminal or two bridging µ 2 -siloxy groups were identified as matching both theoretical and experimental data (Fig.…”
Section: Al Nmr Spectroscopy: a Rendez-vous With Quadrupolar Nucleimentioning
confidence: 99%